Fauna of arboreal Hemiptera in South-Eastern Kazakhstan - KHAKNAZAR KORGANBEK; PERIZAT ESENBEKOVA (Society for Indonesian Biodiversity, 2024)
Abstract. Korganbek K, Esenbekova P. 2024. Fauna of arboreal Hemiptera in South-Eastern Kazakhstan. Biodiversitas 25: 3460-3467. Arboreal hemipterans are a part of the living world, occupying a special place in natural food chain and contact with many living organisms in nature. The purpose of the research is to study and describe the fauna of arboreal hemipterans in the South-Eastern Kazakhstan region. This research was conducted according to various methods generally accepted in the field of entomology. Also materials were processed in laboratory conditions. Samples were collected from 48 locations in South-Eastern Kazakhstan. In total, 939 specimens were collected, including 442 males (47%), 429 females (46%) and 68 nymphs (7%). As a result of the study, 57 species of arboreal hemipterans belonging to 9 families were identified in South-Eastern Kazakhstan. They are Miridae (15 species), Pentatomidae (11 species), Acanthosomatidae (8 species), Lygaeidae (7 species), Anthocoridae (6 species), Nabidae (4 species), Aradidae (4 species), Reduviidae (3 species), Tingidae (2 species). In addition, the article provides information about the nutritional relationships, the number of generations they give per year (voltinism), and the habitats of arboreal hemipterans. Information about the biology of arboreal hemipterans plays an important role in assessing the stability of the biodiversity in the area where they live.